Noninvasive Ventilation in Newborns ≤ 1,500 g after Tracheal Extubation: Randomized Clinical Trial - Ribeiro, Simone Nascimento Santos; Fontes, Maria Jussara Fernandes; Bhandari, Vineet; Resende, Camilla Borges; Johnston, Cintia (American Journal of Perinatology, 2017)
Objective Our aim was to compare the success of extubation in neonates managed with nonsynchronized intermittent nasal positive-pressure ventilation (nsNIPPV) and two modes of nasal continuous positive airway pressure (NCPAP) after the first extubation.Study Design Randomized controlled clinical trial conducted in the neonatal intensive care unit (NICU) included infants with gestational age ≤ 34 weeks and birth weights (BW) 500 to 1,500 g with a diagnosis of respiratory distress syndrome (RDS), divided into three groups: ventilation with nsNIPPV, bubble-NCPAP, and ventilator-NCPAP. Extubation failure (EF) was defined as occurring within 48 hours after extubation.Results We included 101 newborns: nsNIPPV (n = 36); bubble-NCPAP (n = 32) ventilator-NCPAP (n = 33). Overall, the extubation success rate was 81.2%. There were no skin, gastric, or pulmonary complications related to noninvasive ventilation (NIV) (p = 1). There was no difference between the groups regarding the success/EF (p = 0.4). There was extubation success in 81 (81.2%) cases, and EF occurred in 20 (19.8%), associated with longer invasive mechanical ventilation time (p < 0.001) and development of bronchopulmonary dysplasia (p = 0.04).Conclusion In this trial, three modalities of NIV applied in the success/failure outcomes of extubation avoided reintubation in 80% of infants.
Keywords: newborn; preterm; extubation; noninvasive ventilation; respiratory distress syndrome